2017
DOI: 10.1557/jmr.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

3-D characterization of incipient spallation response in cylindrical copper under sweeping detonation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In order to select the elongated voids, a filter with sphericity settings between 0 and 0.3 was applied [ 40 , 77 , 78 , 79 ]. The void distribution along the ROI for each built direction is shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to select the elongated voids, a filter with sphericity settings between 0 and 0.3 was applied [ 40 , 77 , 78 , 79 ]. The void distribution along the ROI for each built direction is shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…For spallation, the early researches were focused on the effect of the microstructure of materials in single‐phase alloys, such as grain, grain boundary, and inclusion . For example, Furnish and Chhabildas discovered that the void nucleation position of the tantalum samples was related to the initial grain size of the samples—the samples with a grain size of 20 μm had a wider void distribution area than the samples with a grain size of 40 μm.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that intermetallic particles initiated microstructural damage during shock loading and reduced spall strength. Similarly, Yang et al took high‐purity oxygen‐free copper as the object of study and discussed the effects of grain boundary type, grain orientation, and grain size on the spallation behavior of high‐purity copper. However, the influence of phase interface on the nucleation and evolution of dynamic damage in multiphase alloys is still unclear.…”
Section: Introductionmentioning
confidence: 99%